2017
DOI: 10.1186/s12966-017-0529-4
|View full text |Cite
|
Sign up to set email alerts
|

“Are Thai children and youth sufficiently active? prevalence and correlates of physical activity from a nationally representative cross-sectional study”

Abstract: BackgroundChildren and youth gain multiple health benefits from regular participation in physical activity (PA). However, in Thailand there is limited national data on children and youth’s PA behaviors and recent reports suggest that Thai children and youth have low levels of PA. Furthermore, there is almost no data on the factors associated with inactivity to support the development of a Thai National PA Plan. The purpose of this paper is to investigate Thai children and youth’s participation in PA and its co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 28 publications
2
12
0
1
Order By: Relevance
“…Children and youth living in urban are less physically active compared to their rural counterparts, especially where the road safety and connectivity is lacking. 27 , 28 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Children and youth living in urban are less physically active compared to their rural counterparts, especially where the road safety and connectivity is lacking. 27 , 28 …”
Section: Discussionmentioning
confidence: 99%
“…The findings of the study also suggested that Thai children are lacking the opportunity to play because the unsafe and unfriendly community environment have restricted parents to allow their children to play outside. 29 , 30 Moreover, a high proportion of Thai children and youth engaged more in screen-time activities 27 as the digital media is widely available and more affordable for Thai families, 31 , 32 , 33 and television viewing and playing electronic game is common to keep the children inside the house. 31 , 34 …”
Section: Discussionmentioning
confidence: 99%
“…Inclusion of explanatory variables in each regression model was guided by the literature. Potential confounders including sex, age, BMI, and region were selected based on previous research [ 30 ], and were accounted for in the multivariable regressions. The descriptive statistics and Chi-square or t-tests were performed in SPSS v26, and all regressions were conducted in STATA v15.…”
Section: Methodsmentioning
confidence: 99%
“…6 Among Asian countries, according to the WHO Global Health Observatory data (from the GSHS), Southeast Asian countries had a distinctly higher prevalence of meeting recommended MVPA level (26.6%) than did Japan. 32 For example, although the age classification was different, Amornsriwatanakul et al conducted a survey using a validated questionnaire among 13,225 Thai children and youth aged 6-17 years, 33 and 23.4% met recommended MVPA level (vs 20.1% in Japan). As mentioned above, to the best of our knowledge, no study has yet examined the prevalence of meeting recommended MVPA level at the population level in Japan.…”
Section: Prevalence Of Moderate-to-vigorous Physical Activity That Mementioning
confidence: 99%